Designing for experiential access to spring water: focusing on inclusivity, ecology & education - de Waal, Christa (School of Architecture, Planning and Geomatics, 2021)
In 2018 water scarcity caused people from all races, cultures and ages to visit allocated springs in Cape Town to collect spring water for everyday use. These water points were insufficient, over-utilized and inappropriately designed causing long queues and disputes about water. The purpose of this research is to address the need to design spaces that will make access to spring water easy and enjoyable. Spring water has the potential to become the binding element that brings people from all walks of life together to celebrate (heritage & play) and utilize spring water. The approach of the project The project synthesises three important aspects. Firstly by creating strong connections between natural flowing spring water and water collection points, the connection between water from a tap and natural spring water is made visible. Secondly opportunities to experience and explore wetland systems will evoke curiosity and educate the public about on-site, ecological water treatment systems. This will include using water on site for irrigation. Thirdly children will be encouraged to actively play and experience the water with heightened sensitivity to the gift of this precious element. The researcher believes that the management of spring water within Cape Town is critical for long term sustainability in the light of climate induced changes in the global south. Cape Town with Table Mountain and the number of springs rising up in this landscape has a valuable resource to be cared for and distributed with respect for the health and well being of all.